Genetic study of 12 X-STRs in Malay population living in and around Kuala Lumpur using Investigator Argus X-12 kit - Samejima, M.; Nakamura, Y.; Nambiar, P.; Minaguchi, K. (2012)
We investigated 12 X-chromosomal short tandem repeat (STR) polymorphisms in 283 unrelated Malay individuals (160 males and 123 females) living in and around Kuala Lumpur using the Investigator Argus X-12 kit. Heterozygosity among the present 12 X-STRs showed a distribution of from 55.3 to 93.5 . The diversity values of the haplotypes constructed using four closely linked groups were all higher than 0.9865. A comparison of allelic frequency in each system and haplotype variation indicated that the nature of these X-STRs in the Malay population differed from that in East Asian, European, or African populations. Several microvariant alleles found in the Malay population were characterized and compared with known sequence data. The present data may be helpful in forensic casework such as personal identification and kinship testing in the Malay population in Malaysia.